Hydrophilic and hydrophobic interactions in concentrated aqueous imidazole solutions: a neutron diffraction and total X-ray scattering study. Issue 9 (19th February 2020) - Al-Madhagi, Laila H.; Callear, Samantha K.; Schroeder, Sven L. M.
Abstract : A study of 5 M aqueous imidazole solutions combining neutron and X-ray diffraction with EPSR simulations shows dominance of hydrogen-bonding between imidazole and water and negligible hydrogen-bonding between imidazole molecules. Abstract : The intermolecular interactions in concentrated (5 M) aqueous imidazole solutions have been investigated by combining neutron diffraction with isotopic substitution, total X-ray scattering and empirical potential structure refinement (EPSR) simulations using a box containing 5530 water and 500 imidazole molecules. The structural model with the best fit was used to generate radial distribution functions and spatial density functions. The local volume surrounding imidazole molecules is dominated by water, due to strong hydrogen-bonding between the nitrogen moieties of imidazole and water molecules; within a radius of 6.4 Å from the central imidazole molecule there are, on average, 17 water and only 3 imidazole molecules. Even though imidazole interacts with water it appears to disrupt hydrogen bonding in the surrounding water network only minimally. Hydrogen-bonding between imidazole molecules is negligible. The most probable positions of imidazole nearest-neighbours are above and below the plane of the aromatic ring. At low distances (up to ∼3.5–3.8 Å) these nearest neighbours were found to prefer parallel orientation of the molecular planes, indicating hydrophobic (π–π) stacking. At longer distances (up to ∼5 Å), imidazole neighbours assume both parallel and edge-to-face orientations. Overall, hydrated imidazole molecules are the most probable structural motif in aqueous solutions, with very few direct imidazole–imidazole interactions.